A Pragmatic Study of Sarcasm in Netizen Comments - Sosiana Sosiana (Sean Institute, 2026)
Sarcasm has become a prominent linguistic phenomenon in digital communication, particularly in netizen comments on social media platforms. The absence of face-to-face interaction and non-verbal cues encourages users to employ indirect and implicit language strategies, including sarcasm, to express criticism, dissatisfaction, and social attitudes. This study aims to examine sarcasm in netizen comments from a pragmatic perspective in order to understand how meaning is constructed beyond literal interpretation. The research adopts a descriptive qualitative approach using a literature review method. Data were collected from relevant books, peer-reviewed journals, and previous studies focusing on pragmatics, sarcasm, and digital discourse. The analysis synthesizes theoretical concepts and empirical findings related to sarcasm as a pragmatic strategy in online communication. The results indicate that sarcasm functions as an indirect speech act influenced by contextual factors such as social norms, shared knowledge, and communicative intentions. Sarcasm is commonly used to convey criticism, express emotions, and negotiate social identity in digital spaces. In conclusion, the study highlights the importance of pragmatic analysis in interpreting sarcastic expressions in netizen comments and contributes to a deeper understanding of meaning-making processes in online discourse.